Michigan State University contributions to international business and innovation - Cavusgil, S. Tamer (JAI Press, 2009)
Volume 19 of "Advances in International Marketing" is quite unique. It features essays in marketing and international business, written by doctoral alumni of Michigan State University. Based on the 2008 symposium held at Michigan State University (MSU), the authors offer personal reflections of the contributions their mentors, peers, and the larger academic community have made to their professional development. These deliberations serve to illustrate how individual research streams, whose foundations were established during the doctoral program, took off and became primary areas of specialization for individual alumni. The collective contribution of MSU doctoral alumni to the fields of international business and innovation/new products is truly remarkable. Such high visibility of MSU alumni in the international business literature undoubtedly is a major reason why MSU continues to receive high marks and rankings in academic circles.
"Based on the 2008 symposium held at MSU"--P. [4] of cover.
Keywords: Michigan State University.; Business education -- Congresses.; Business schools -- Congresses.; Higher & further education, tertiary education.; Industrial or vocational training.; Business & Economics -- Education.; elektronické knihy; electronic books